Hiss or equatorial noise? Ambiguities in analyzing suprathermal ion plasma wave resonance. Issue 10 (13th October 2016) - Sarno‐Smith, Lois K.; Liemohn, Michael W.; Skoug, Ruth M.; Santolik, Ondrej; Morley, Steven K.; Breneman, Aaron; Larsen, Brian A.; Reeves, Geoff; Wygant, John R.; Hospodarsky, George; Kletzing, Craig; Moldwin, Mark B.; et al.
Abstract: Previous studies have shown that low‐energy ion heating occurs in the magnetosphere due to strong equatorial noise emission. Observations from the Van Allen Probes Helium Oxygen Proton Electron (HOPE) instrument recently determined that there was a depletion in the 1–10 eV ion population in the postmidnight sector of Earth during quiet times at L < 3. The diurnal variation of equatorially mirroring 1–10 eV H + ions at 2 < L < 3 is connected with similar diurnal variation in the electric field component of plasma waves ranging between 150 and 600 Hz. Measurements from the Van Allen Probes Electric and Magnetic Field Instrument Suite and Integrated Science (EMFISIS) data set are used to analyze waves of this frequency in near‐Earth space. However, when we examine the polarization of the waves in the 150 to 600 Hz range in the equatorial plane, the majority are right‐hand polarized plasmaspheric hiss waves. The 1–10 eV H + equatorially mirroring population does not interact with right‐hand waves, despite a strong statistical relationship suggesting that the two are linked. We present evidence supporting the relationship, both in our own work and the literature, but we ultimately conclude that the 1–10 eV H + heating is not related to the strong enhancement of 150 to 600 Hz waves. Key Points: A 1–10 eV ion loss from plasma wave interaction High‐amplitude plasma waves seem like probable candidate Polarization analysis reveals that the waves are hiss